Motion recognition by a liquid filled tubular triboelectric nanogenerator. Issue 2 (13th December 2018) - Yuan, Zuqing; Du, Xinyu; Niu, Huidan; Li, Nianwu; Shen, Guozhen; Li, Congju; Wang, Zhong Lin
Abstract : A liquid-polymer tubular triboelectric nanogenerator constructed by combing conductive liquid and a stretchable elastomer tube to achieve multifunctional sensing. Abstract : The development of flexible electronics has extended the limit of the intelligent devices, which are highly sensitive, soft and capable of sustaining arbitrary deformation. Here, we report a liquid-polymer tubular triboelectric nanogenerator (L-P TENG) that is filled with liquid for a shape-adaptive sensor in various working modes. The L-P TENG is based on liquid–solid contact electrification with the use of displacement current and excited by the shape change of the tubular structure. The high softness of the device makes it possible to be twisted to any curve and bear extreme strain. It can be used to detect a slight difference in pressure from touch, pressing and stretching and is suitable for a wide-range force recognition with high sensitivity. The independent and multifunctional properties of the L-P TENG extend the potential applications through combinations. Such assembled units with crossings can sense the approaching object. This study provides a new direction for flexible electromechanical sensing and has potential applications in self-powered sensors, wearable electronics, smart human–machine interaction and auxiliary motion correction.